Can people with longstanding bulimia nervosa suffer from severe and enduring eating disorder? A qualitative study - Paul H Robinson; Giulia Guidetti; Jessica Kasriel; Jomana Khawandanah; Maxine Hughes; Zeinab Hachem (Journal of Eating Disorders)
Abstract Objectives To interview a series of individuals with bulimia nervosa of longstanding to establish their symptoms and examine the suggestion, using qualitative analysis, that the term “Severe and Enduring Bulimia Nervosa (SEED-BN)” might be appropriate and helpful. Methods 12 participants with Bulimia Nervosa, one male, were interviewed with the help of an interview guide. Interviews were recorded and transcribed. Transcripts were analysed using Thematic Analysis. Results Participants with Bulimia Nervosa described serious problems in many realms, especially social, psychological, family and relationships. Conclusions Bulimia nervosa of long duration is associated with many serious symptoms. It seems likely that recognition of long-standing bulimia nervosa as a severe and enduring eating disorder could encourage clinicians and families to pay attention to the wide variety of problems suffered by this group. Further research is required to examine this proposal.